2021
DOI: 10.3390/ijerph18168759
|View full text |Cite
|
Sign up to set email alerts
|

Morale and Perceived Threats as Predictors of Psychological Coping with Distress in Pandemic and Armed Conflict Times

Abstract: The present study investigated predictors of psychological coping with adversity responses during the COVID-19 pandemic and an armed conflict. Two paired samples that represented the Israeli population that was exposed to both adversities were compared. Respondents rated five different psychological coping responses associated with the two adversities, such as anxiety or individual resilience. Perceived security, pandemic, economic, and political risks, as well as level of morale, were rated. Two major finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“… 23 Eshel et al analysed the interaction between various aspects of mental health, but did not directly report differences in health for the two periods. 24 In addition, the involvement of the Israeli study population in the conflict was much more direct than the situation analysed in our study.…”
Section: Discussionmentioning
confidence: 51%
“… 23 Eshel et al analysed the interaction between various aspects of mental health, but did not directly report differences in health for the two periods. 24 In addition, the involvement of the Israeli study population in the conflict was much more direct than the situation analysed in our study.…”
Section: Discussionmentioning
confidence: 51%
“…All these aspects show the impact of the armed conflict at a distance from the place of its occurrence. Several recent studies have objectively shown the impact of disasters on the mental health of victims but also on those involved in rescuing victims [ 1 , 2 , 15 ]. Continuing this idea of the impact of armed conflict, our study brings objective data that show that the level of stress increases beyond the borders where the war takes place, indirectly affecting the medical staff involved in the care of victims.…”
Section: Discussionmentioning
confidence: 99%
“…In the aftermath of catastrophes and disasters (e.g., mass shootings, hurricanes, terrorism, floods), people respond with a variety of negative psychological outcomes, including depression, anxiety, traumatic stress, etc. [ 1 , 2 ]. An atypical polytraumatic event for the 21st century started on 24 February 2022, when Ukraine was attacked and invaded by the Russian army.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the pandemic, the messages relayed to the public were mostly focused on the assumption that the population is concerned with the virus and its potential consequences on health status. In contrast, longitudinal studies have shown that the highest concern of the population throughout the pandemic was the political instability that characterized the Israeli society rather than the health threat [ 10 , 24 ]. Another misconception was based on the conception that as the elderly population was considered (and accurately so) as the most vulnerable to the virus (along with other populations of special needs), it is also the least resilient sector in society.…”
Section: Insight 2: Don’t Assume! Look For Evidence-based Datamentioning
confidence: 99%
“…Another phenomenon to be noted is the comparison of the mean levels of resilience among students in academic institutions to the general public. Whilst many decision-makers believed that students are ‘less impacted’ by the pandemic, studies showed that the mean level of individual resilience among students is lower compared to that of the general population, while their level of distress was higher [ 10 ].…”
Section: Insight 2: Don’t Assume! Look For Evidence-based Datamentioning
confidence: 99%